5-(t+6)=-1+2(t-3)

Simple and best practice solution for 5-(t+6)=-1+2(t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(t+6)=-1+2(t-3) equation:


Simplifying
5 + -1(t + 6) = -1 + 2(t + -3)

Reorder the terms:
5 + -1(6 + t) = -1 + 2(t + -3)
5 + (6 * -1 + t * -1) = -1 + 2(t + -3)
5 + (-6 + -1t) = -1 + 2(t + -3)

Combine like terms: 5 + -6 = -1
-1 + -1t = -1 + 2(t + -3)

Reorder the terms:
-1 + -1t = -1 + 2(-3 + t)
-1 + -1t = -1 + (-3 * 2 + t * 2)
-1 + -1t = -1 + (-6 + 2t)

Combine like terms: -1 + -6 = -7
-1 + -1t = -7 + 2t

Solving
-1 + -1t = -7 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
-1 + -1t + -2t = -7 + 2t + -2t

Combine like terms: -1t + -2t = -3t
-1 + -3t = -7 + 2t + -2t

Combine like terms: 2t + -2t = 0
-1 + -3t = -7 + 0
-1 + -3t = -7

Add '1' to each side of the equation.
-1 + 1 + -3t = -7 + 1

Combine like terms: -1 + 1 = 0
0 + -3t = -7 + 1
-3t = -7 + 1

Combine like terms: -7 + 1 = -6
-3t = -6

Divide each side by '-3'.
t = 2

Simplifying
t = 2

See similar equations:

| 3s^2-8s-11=0 | | -2n-29=3(1-6n) | | 5(2*x-3)=15 | | .75x=190 | | 5(1-7b)=2b-32 | | 3(-5a+7)=111 | | 5x^2+x^3=6 | | (5k^4+5)-(4k^3-2k^4)= | | 3(x-7)+2x=5(x+4)-41 | | 3(x-1)=-(x-5) | | 22x+22=118 | | -23=-2*a-10+a | | 8h^2+14h+5=0 | | 3(-5a+7)=11 | | 11m+13n=209 | | 5*12=9(3x+2) | | 5(a+b)=5a+5b | | 12-2x=9x+45 | | 5(x+8)+3=5x+6 | | 3x+6(4x+8)=180 | | 3n+(-7)=2n-72 | | -(3b-15)=6 | | 4-70=12+2 | | .60x=228 | | xy=360 | | 4x-1=4+7 | | -21-n=3(-5n+7) | | (x+9)(3x)=(x+9)(6) | | 1=3(2m+5)+2(3m+5) | | 13=5+3*b-13 | | 5x-25-x-7=4x-32 | | 2/3(3x+3)=8 |

Equations solver categories